2014
DOI: 10.1016/j.baga.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Potentiated gene regulation by methylphenidate plus fluoxetine treatment: Long-term gene blunting (Zif268, Homer1a) and behavioral correlates

Abstract: Use of psychostimulants such as methylphenidate (Ritalin) in medical treatments and as cognitive enhancers in the healthy is increasing. Methylphenidate produces some addiction-related gene regulation in animal models. Recent findings show that combining selective serotonin reuptake inhibitor (SSRI) antidepressants such as fluoxetine with methylphenidate potentiates methylphenidate-induced gene regulation. We investigated the endurance of such abnormal gene regulation by assessing an established marker for alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…FLX potentiates MP-induced regulation of Homer1a to a similar degree as regulation of Zif268 and c- Fos . This was demonstrated for acute IEG induction by MP+FLX (present results) as well as for blunting (repression) of IEG induction after repeated MP+FLX treatment (Beverley et al, 2014; Van Waes et al, 2014). …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…FLX potentiates MP-induced regulation of Homer1a to a similar degree as regulation of Zif268 and c- Fos . This was demonstrated for acute IEG induction by MP+FLX (present results) as well as for blunting (repression) of IEG induction after repeated MP+FLX treatment (Beverley et al, 2014; Van Waes et al, 2014). …”
Section: Discussionsupporting
confidence: 76%
“…In contrast, repeated methylphenidate (dopamine) treatment produced robust Zif268 blunting, but had minimal or no effects for Homer1a (Cotterly et al, 2007). However, as discussed above, adding FLX (serotonin) to MP produced similar blunting for both Homer1a and Zif268 (Beverley et al, 2014; Van Waes et al, 2014). These results highlight the critical role for serotonin in Homer1a regulation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Transcriptomic changes can occur within minutes or hours, and in response to most environmental changes; thus, it could be that some of the 64 differentially expressed transcripts are not directly related to the MPH response, but more generally to the ingestion of different food sources. However, transcriptomic responses to drugs have been reported in animal models (Yano and Steiner 2005;Adriani et al 2006;Beverley et al 2014) and in humans (Schwarz et al 2015), testing alcohol (Ghezzi et al 2013) and methamphetamine (Sun et al 2011) for example. Using a network-based approach, Sun et al (2011) found that methamphetamine, another commonly used drug in the treatment of ADHD (López 2006;Goodman 2007), led to alterations in the expression of genes involved in carbohydrate metabolism, which is consistent with results from our KEGG pathway analysis ( Figure 1D and Table S6).…”
Section: Mph Alters Locomotor Activity and Gene Expression In A Wt Pomentioning
confidence: 99%
“…Zif268/Egr1 expression showed the greatest effect due to MP. 33 The combined group did show pronounced upregulation of MP-induced blunting for both genes; which concluded that SSRIs in combination with MP may increase the risk of developing addiction. 33 The MP+FLX group experienced heightened striatal gene regulation.…”
Section: Resultsmentioning
confidence: 95%